Acculturative and Enculturative Stress, Depressive Symptoms, and Maternal Warmth: Examining Within-Person Relations among Mexican-origin Adolescent Mothers - Zeiders, Katharine H. (Dev Psychopathol, 2014)
Mexican-origin adolescent mothers face numerous social challenges during dual-cultural adaptation that are theorized to contribute to greater depressive symptoms. Alongside challenges, there are familial resources that may offer protection. As such, the current study examined the trajectories of depressive symptoms among 204 Mexican-origin adolescent mothers (M(age) = 16.80, SD = 1.00) across a 4-year period (3(rd) trimester of pregnancy, and 10, 24, and 36 months postpartum). Further, we examined the within-person relations of two unique sources of stress experienced during the dual-cultural adaptation process, acculturative and enculturative stress, and youths’ depressive symptoms; we also tested whether adolescent mothers’ perceptions of warmth from their own mothers emerged as protective. Adolescent mothers reported a decline in depressive symptoms after the transition to parenthood. Acculturative and enculturative stress emerged as significant positive within-person predictors of depressive symptoms. Maternal warmth emerged as a protective factor in the relation between enculturative stressors and depressive symptoms; however, for acculturative stressors, the protective effect of maternal warmth only emerged for U.S.-born youth. Findings illustrate the multi-dimensionality of stress experienced during the cultural adaptation process and a potential mechanism for resilience among Mexican-origin adolescent mothers.